2021
DOI: 10.22141/2224-0721.2.74.2016.70956
|View full text |Cite
|
Sign up to set email alerts
|

Роль Нейтрофильных Лейкоцитов В патогенезе Сахарного Диабета 1-Го Типа У человека (Аналитический Обзор С включением Собственных Данных)

Abstract: Резюме. Проведен анализ современной литературы и результатов собственных исследований, касающихся роли нейтрофилов в организме здорового человека и больного сахарным диабетом 1-го типа (СД-1). Представлены последние данные о содержании, ультраструктуре и функциях (фагоцитоз, нетоз, секреция бактерицидных и иммунорегуляторных соединений) нейтрофилов крови на различных стадиях развития СД-1, начиная с доклинического периода. Особое внимание уделено участию нейтрофилов в различных реакциях естественного и адаптив… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…A small but significant (p < 0.05) increase in the total number of leukocytes was found in the hematological study of patients with T2D before the beginning of their treatment with metformin, as compared to the control group, which agrees with our previous data [32,41], as well as the results of other authors, conducted on extensive clinical material as shown in Table 1. This leukocytosis is mainly due to a significant increase in the absolute number of segmented Note: * -p < 0.05 compared to group of T2D patients before metformin treatment with healthy persons; # -p < 0.05 compared to group of patients before treatment with group of patients after metformin treatment.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A small but significant (p < 0.05) increase in the total number of leukocytes was found in the hematological study of patients with T2D before the beginning of their treatment with metformin, as compared to the control group, which agrees with our previous data [32,41], as well as the results of other authors, conducted on extensive clinical material as shown in Table 1. This leukocytosis is mainly due to a significant increase in the absolute number of segmented Note: * -p < 0.05 compared to group of T2D patients before metformin treatment with healthy persons; # -p < 0.05 compared to group of patients before treatment with group of patients after metformin treatment.…”
Section: Resultssupporting
confidence: 92%
“…At the same time, accor ding to modern ideas, T2D in humans is an inflammatory disease in the pathogenesis of which a key role is played by the natural and adaptive immune system [11]. One of the conclusive evidence is leukocytosis, a significant change in the leukocyte composition and immunologically different subpopulations of blood peripheral (BP) lymphocytes, and also the level of proinflammatory and regulatory cytokines and chemokines in BP of patients with prediabetes and T2D [41].…”
Section: том 13 № 5 2017mentioning
confidence: 99%
“…According to electron microscopic studies, a characteristic feature of neutrophils is the presence of cytoplasmic granules. According to the literature, there are three types of granules: primary or azurophilic, secondary or specific, and tertiary or secretory vesicles [3,28]. Azurophilic granules are electronically dense and larger in size.…”
Section: Discussionmentioning
confidence: 99%
“…They contain acid hydrolases, cathepsin C, bactericidal proteins (defensins, sergocidins, catemicidins), myeloperoxidase and neutrophil elastase. The latter can directly destroy the interndothelial junctions, breaking down surface proteins, which leads to increased vascular permeability [17,25,28]. Increased permeability of the endothelium of hemocapillaries of the alveolar wall is accompanied by the release of NG into the interstitium and lumen of the alveoli.…”
Section: Discussionmentioning
confidence: 99%